Class-Based Weighted Fair Queuing Scheduling on Dual-Priority Delta Networks. (5th April 2012) - Vasiliadis, D. C.; Rizos, G. E.; Vassilakis, C.
Abstract : Contemporary networks accommodate handling of multiple priorities, aiming to provide suitable QoS levels to different traffic classes. In the presence of multiple priorities, a scheduling algorithm is employed to select each time the next packet to transmit over the data link. Class-based Weighted Fair Queuing (CBWFQ) scheduling and its variations is widely used as a scheduling technique, since it is easy to implement and prevents the low-priority queues from being completely neglected during periods of high-priority traffic. By using this scheduling, low-priority queues have the opportunity to transmit packets even though the high-priority queues are not empty. In this work, the modeling, analysis and performance evaluation of a single-buffered, dual-priority multistage interconnection network (MIN) operating under the CBWFQ scheduling policy is presented. Performance evaluation is conducted through simulation, and the performance measures obtained can be valuable assets for MIN designers, in order to minimize the overall deployment costs and delivering efficient systems.